Le silence des limites dans la littérature: Deux exemples :Michel de Montaigne et Marguerite Duras - Timénova, Zlatka (2012)
The paper studies the concept of limit in literary discourse. Two aspects are discussed: 1) the limit as a necessary structuring element in the process of verbal nomination; 2) the limit as a verbal constraint which appeals to be defeated in case of extreme experience, as death, love, desire, Shoah. We analyse two examples dealing with the language restriction in the literary practice: Montaignes’ essays and Duras’ novels. Montaigne adopts a specific style of unlimited judgements and topics accumulation in a spontaneous order and logic with the purpose of revealing the deepest profile of human nature. Duras practices a minimalist writing that ruins the linear syntactic structure and the narrative model, achieving an effect of silence thus providing the possibility of unlimited meaning.